2017
DOI: 10.1002/adfm.201700121
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Top‐Surface Multilayer/Single‐Crystal Graphene Growth by “Gettering” Carbon Diffusion at Backside of the Copper Foil

Abstract: A unique strategy is reported to constrain the nucleation centers for multilayer graphene (MLG) and, later, single‐crystal graphene domains by gettering carbon source on backside of the flat Cu foil, during chemical vapor deposition. Hitherto, for a flat Cu foil, the top‐surface‐based growth mechanism is emphasized, while overlooking the graphene on the backside. However, the systematic experimental findings indicate a strong correlation between the backside graphene and the nucleation centers on the top‐surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 49 publications
(67 reference statements)
3
33
0
Order By: Relevance
“…This effect can be elevated further using a nickel foam backing instead of nickel plate, slowing the growth rate even more (Figure S4, Supporting Information). The discrepancy between hBN growth on Cu/quartz and Cu/nickel is similar to that observed for carbon gettering growth of graphene . Therefore, our results indicate a similar gettering mechanism for boron species can be realized by the nickel support on the backside of the Cu foil during CVD growth of hBN.…”
Section: Comparison Of Emission Energy and Density Of Cvd Hbn Spes Insupporting
confidence: 79%
“…This effect can be elevated further using a nickel foam backing instead of nickel plate, slowing the growth rate even more (Figure S4, Supporting Information). The discrepancy between hBN growth on Cu/quartz and Cu/nickel is similar to that observed for carbon gettering growth of graphene . Therefore, our results indicate a similar gettering mechanism for boron species can be realized by the nickel support on the backside of the Cu foil during CVD growth of hBN.…”
Section: Comparison Of Emission Energy and Density Of Cvd Hbn Spes Insupporting
confidence: 79%
“…(111) facets reportedly gave faster graphene growth with fewer adlayers compared to facets with other orientations,8b,f and this was stated as possibly being due to a higher diffusion rate of carbon species on Cu(111),8f,9 and the smooth surface of such facets was also proposed to suppress adlayer formation 8b. Another approach has recently been reported that yielded single layer graphene with very few adlayers by restricting the diffusion of carbon from the backside of the Cu foil using a Ni support substrate . Although the density of adlayers was suppressed by these strategies, a clear picture of the mechanism(s) for generating few‐ to no‐adlayer graphene by CVD has not been obtained, and a reliable and controllable approach is needed for the growth of single layer graphene that never contains adlayers.…”
mentioning
confidence: 99%
“…We then attempt to hinder the FLG nucleation by using a Ni foil, serving as a C sink, to support the Cu substrates. 40,41 As seen in Figure S5e, this trial has failed, possibly because the Cu and Ni foils are not perfectly flat and in intimate contact with each other, leaving gaps for CH4 to diffuse through Cu. Another group has used a W foil inside a Cu enclosure for the same purpose.…”
Section: Resultsmentioning
confidence: 99%